Toward a Cognitive Classical Linguistics The Embodied Basis of Constructions in Greek and Latin - Mocciaro, Egle (De Gruyter, 2019)
Building on the momentum enjoyed by cognitive-functional approaches within Classics, this volume gathers a series of papers that bring the study of grammatical and syntactic constructions in both Greek and Latin under the perspective of theories developed in cognitive linguistics, revealing the role of human embodiment in determining the meanings of various linguistic phenomena.